2001
DOI: 10.1603/0022-0493-94.5.1128
|View full text |Cite
|
Sign up to set email alerts
|

New Tachinidae (Diptera) Host Records of Eastern North American Forest Canopy Lepidoptera: Baseline Data in a <I>Bacillus thuriengiensis</I> Variety <I>kurstaki</I> Nontarget Study

Abstract: Macrolepidopteran caterpillars collected in 1995 and 1996 in the Monongahela National forest, Pocahontas County, WV, and the George Washington National forest, Augusta County, VA, yielded 60 previously unreported tachinid host associations. Most associations were between native species, but the introduced polyphagous tachinid Compsilura concinnata (Meigen) produced eight new associations with native hosts. The tachinids collected were slightly broader in their host preferences than associated Braconidae and Ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 7 publications
(3 reference statements)
0
18
0
1
Order By: Relevance
“…However, M. americanum was heavily parasitized by tachinids (42%) (Strazanac et al 2001), and several hymenopteran parasitoids have been reported from larvae of this species (Kulman 1965, Witter and Kulman 1972, Krombein et al 1979). The number of hymenopteran parasitoid species parasitizing macrolepidopteran larvae ßuctuated during the collecting seasons, with the largest number collected in late May to early June (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, M. americanum was heavily parasitized by tachinids (42%) (Strazanac et al 2001), and several hymenopteran parasitoids have been reported from larvae of this species (Kulman 1965, Witter and Kulman 1972, Krombein et al 1979). The number of hymenopteran parasitoid species parasitizing macrolepidopteran larvae ßuctuated during the collecting seasons, with the largest number collected in late May to early June (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Krombein et al (1979) included many previously unpublished associations, whereas Arnaud (1978) was based on previously published records. Recent large-scale rearings of forest macrolepidoptera by Butler (1993) documented 115 new host associations and our companion study by Strazanac et al (2001), which reported 60 new tachinid host associations, indicate that we lack a considerable amount of knowledge in this area of forest ecology.…”
mentioning
confidence: 90%
“…Los Tachinidae son importantes parasitoides de Lepidoptera, así como de otros órdenes de insectos (Strazanac et al 2001). En el presente estudio, las especies pertenecientes a esta familia de dípteros se caracterizan por ser parasitoides primarios y koinobiontes y todos los parasitoides identifi cados representan nuevos registros de parasitismo sobre H. metabus, con la excepción de Belvosia spp.…”
Section: Discussionunclassified
“…We reared C. concinnata from eight identified host species, five of which were known hosts and three of which represent new rearing records (Table S3 in Online Resource 1). Of the remaining total 105 lepidopteran species collected in our study, 11 are known to be hosts of the introduced tachinid (Raizenne 1952;Arnaud 1978;Peigler 1994;Cossentine and Jensen 1995;Strazanac et al 2001) but did not produce any adult C. concinnata in our rearings.…”
Section: Parasitism Rates and Parasitoid Sharingmentioning
confidence: 96%